Breaking mirrors - you're more than what you see - Mahony, Yan An Margaret (2018)
Breaking Mirrors: You’re More Than What You See is a health communication campaign targeted at prevention of anorexia and bulimia. Developed by four final year undergraduates from the Wee Kim Wee School of Communication and Information at Nanyang Technological University (NTU), this campaign aims to reduce body dissatisfaction and thin body idealisation, which are major risk factors for the development of both anorexia and bulimia. The campaign targets female university students in Singapore aged 18 - 24 who are at high risk of developing anorexia and bulimia. Studies show that young women are disproportionately affected by body dissatisfaction, with transitional and stressful phases such as university making them more susceptible to developing eating disorders. Our strategy aims to motivate our target audience to embrace themselves and encourage others around them to do the same. To engage the target audience, we have used narratives of eating disorder survivors and medical health experts on social media, supplemented by a range of activities at our roadshows on university campuses. This report details the primary and secondary research that forms the foundation of this campaign. It delineates the planning and execution of the tactics, followed by an extensive overview of the process and outcome evaluation. Lastly, the report analyses the effectiveness of the campaign, followed by a discussion of its strengths, recommendations for improvement and future directions. Original documents, including campaign collaterals, event photographs, and other relevant research data and results have been included in the appendices to supplement the main paper.